Association of the Quality of Interpersonal Care During Family Planning Counseling With Contraceptive Use. Issue 6 (June 2016) - Dehlendorf, Christine; Henderson, Jillian T.; Vittinghoff, Eric; Grumbach, Kevin; Levy, Kira; Schmittdiel, Julie; Lee, Jennifer; Schillinger, Dean; Steinauer, Jody
Abstract : (Abstracted from Am J Obstet Gynecol 2016; DOI: 10.1016/j.ajog.2016.01.173) Over the past several decades, the proportion of unintended pregnancies in the United States has remained high at approximately 50%. Interactions of reproductive-age women with family planning providers are an opportunity to contribute to women's ability to use contraception consistently and effectively, decreasing their risk of unintended pregnancy.